Filosofia ‘e’ letteratura: l’avvenire di una congiunzione - Canullo, Carla (Itinerari, 2024)
To analyse the lemma ‘philosophy of literature’, this paper proposes to separate philosophy and literature to understand the conjunction ‘and’ as a way of grasping what is ‘common’ between philosophy and literature. To do this, it will first consider the etymology of the term ‘common’ and the different meanings of the term munus. Secondly, it will look at the different ways in which literature and philosophy can stand together. Thirdly, it will propose to understand the meaning of ‘in common’, which is what literature and philosophy give each other because each has what the other ‘misses’. French philosophers and novelists Henry, Delecroix and Aubry provide examples of this possibility which will be analysed in the final section of the paper. Thus, the conjunction that can bond literature ‘and’ philosophy will be understood in terms of how they can both expose and reopen matters to which they continue to give a ‘future’ by narrating and understanding them – the future of a conjunction.